Impact of Gender on Symptoms and Comorbidities in Obstructive Sleep Apnea - BALCAN, MEHMET BARAN (AVES, 2021)
Objective: Obstructive sleep apnea (OSA) is more common in men than in women. In this study, we aimed to address the impact of gender on symptoms and comorbidities in patients with OSA. Materials and Methods: This cross-sectional study was conducted among 1,317 consecutive patients, who were admitted to the Sleep Apnea Clinic of the Marmara University Hospital between November 2015 and October 2018, and who completed questionnaires and a sleep study with cardiorespiratory polygraphy. OSA was defined as Apnea Hypopnea Index (AHI) >= 15/hour. Results: In all, 1,042 patients (334 women) fulfilled the inclusion criteria. OSA was observed in 589 patients (56.5%). Women were older than men (50.2 +/- 12.5 versus 45.6 +/- 15.1 years) and had lower AHI (22.1 +/- 20.1 versus 26.8 +/- 21.9 events/h). In the OSA group, women were older (53.7 +/- 11.5 versus 47.8 +/- 12.8 years) and more obese (BMI 34.6 versus 31.8 kg/m(2)). Symptoms were categorized as frequent/very frequent, and women with OSA complained more about daytime fatigue (74.6% versus 63.7%), nocturia (69.7% versus 51.8%), headache in the morning (50.0% versus 28.4%), depressive mood (49.0% versus 19.5%), and restless legs symptoms (43.1% versus 17.2%), than did men (all p values <0.05). Comorbidities were observed more in women than in men (lung disease [25.4% versus 13.7%], hypertension [29.6% versus 15.0%], diabetes [20.3% versus 11.3%], and hypothyroidism [14.0 % versus 4.1%]). In regression analysis, age (OR 1.03, p<0.001), BMI (OR 1.13, p<0.001), and male sex (OR 2.08, p<0.001) were significantly predictive for OSA while history of tonsillectomy was protective (OR 0.48, p=0.033). Conclusion: Fatigue, nocturia, headache, depressive mood, restless leg, and comorbidities were observed more in women. OSA-related symptoms develop late and/or the referral of women for diagnostic evaluation of OSA is delayed. Symptoms and comorbidities in women should be evaluated more attentively for earlier referral and diagnosis of OSA.
Keywords: Obstructive sleep apnea; gender difference; symptoms; comorbidities; CLINICAL PRESENTATION; DAYTIME SLEEPINESS; EPIDEMIOLOGY; POPULATION; SEVERITY; SEX